2011
DOI: 10.1111/j.1439-0310.2011.02009.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual Variation in Behavioural Reactions to Unfamiliar Conspecific Vocalisation and Hormonal Underpinnings in Male Chimpanzees

Abstract: It has been established that various species exhibit personality, defined as intra‐individual consistency and inter‐individual variation in behavioural phenotypes. For example, certain individuals may demonstrate consistently greater behavioural reactions and elevated stress responses. We conducted playback experiments and hormonal analyses on male chimpanzees (Pan troglodytes) in captivity to investigate the patterns and proximate mediators of individual variations in behavioural reactions. We found intra‐ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 65 publications
3
24
0
Order By: Relevance
“…Similarly, at Ngogo, males EL and HO had unusually high patrolling rates (Watts & Mitani 2001). Recent playback experiments in captivity showed ‘intra-individual consistency and inter-individual variation in behavioural reactions…to vocalisations by unfamiliar chimpanzees’ (Kutsukake et al 2012, page 269). Although Wilson et al (2001) found no difference among males at Kanyawara in the likelihood of responding to simulated calls of strangers (except when impact hunter MS stayed behind to mate-guard a female), low-ranking males were less likely to travel to the periphery of the community range (Wilson et al 2012).…”
Section: Hypotheses and Predictionsmentioning
confidence: 99%
“…Similarly, at Ngogo, males EL and HO had unusually high patrolling rates (Watts & Mitani 2001). Recent playback experiments in captivity showed ‘intra-individual consistency and inter-individual variation in behavioural reactions…to vocalisations by unfamiliar chimpanzees’ (Kutsukake et al 2012, page 269). Although Wilson et al (2001) found no difference among males at Kanyawara in the likelihood of responding to simulated calls of strangers (except when impact hunter MS stayed behind to mate-guard a female), low-ranking males were less likely to travel to the periphery of the community range (Wilson et al 2012).…”
Section: Hypotheses and Predictionsmentioning
confidence: 99%
“…Salivary, but not urinary or faecal samples reflect acute changes in plasma hormones. The short time lag between changes in plasma and salivary hormone concentrations enables investigation of the effect of social events on hormonal levels (see also Hohmann et al, ; Kutsukake et al, ; Wobber et al, ). As the use of saliva samples becomes more common, it may be possible to investigate the manner in which social events, in addition to the presence of females, affect individual hormonal concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…All males were wild‐born and imported to Japan in 1982 and have been living in the current facility since 2000; the study group was formed in June 2003. For further information on our previous hormone and behavior studies conducted in this institute, see Kutsukake et al (, ) and Yamamoto et al ().…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations